Mechanism of Thiazide Diuretic Arterial Pressure Reduction: The Search Continues - Rapoport, Robert M.; Soleimani, Manoocher (Frontiers in Pharmacology, 2019)
Thiazide diuretic (TZD)-mediated chronic reduction of arterial pressure is thought to occur through decreased total peripheral vascular resistance. Further, the decreased peripheral vascular resistance is accomplished though TZD activation of an extrarenal target, resulting in inhibition of vascular constriction. However, despite greater than five decades of investigation, little progress has been made into the identification of the TZD extrarenal target. Proposed mechanisms range from direct inhibition of constrictor and activation of relaxant signaling pathways in the vascular smooth muscle, to indirect inhibition through decreased neurogenic and hormonal regulatory pathways. Surprisingly, particularly in view of this lack of progress, comprehensive reviews of the subject are absent. Moreover, even though it is well recognized that 1) several types of hypertension are insensitive to TZD reduction of arterial pressure and, further, TZD fail to reduce arterial pressure in normotensive subjects and animals, and 2) different mechanisms underly acute and chronic TZD, findings derived with these models and procedures remain largely undifferentiated. This review 1) comprehensively describes findings in the area; 2) differentiates between observations in TZD-sensitive and -insensitive hypertension, normotensive subjects/animals, and acute and chronic effects of TZD; 3) critically evaluates proposed TZD extrarenal targets; 4) proposes guiding parameters for relevant investigations into extrarenal TZD target identification, and 5) proposes a working model for TZD chronic reduction of arterial pressure through vascular dilation.